2008
DOI: 10.1016/j.healthplace.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating options for measurement of neighborhood socioeconomic context: Evidence from a myocardial infarction case–control study

Abstract: We hypothesized that neighborhood socioeconomic context would be most stronly associated with risk of myocardial infarction (MI) for smaller "neighborhood" definitions. We used data on 487 nonfatal, incident MI cases and 1,873 controls from a case-control study in Washington State. Census data on income, home ownership, and education were used to estimate socioeconomic context across four neighborhood definitions: one-kilometer buffer, block group, census tract, and ZIP code. No neighborhood definition led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 66 publications
5
34
1
Order By: Relevance
“…We explored differences in model fit at each neighborhood size. As in a simulation study (Spielman and Yoo, 2009) and a previous empirical study (Lovasi, et al, 2008), buffer size had little impact on model fit. Furthermore, model fit for White women was much higher than for minority race/ethnic groups (Table 3).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We explored differences in model fit at each neighborhood size. As in a simulation study (Spielman and Yoo, 2009) and a previous empirical study (Lovasi, et al, 2008), buffer size had little impact on model fit. Furthermore, model fit for White women was much higher than for minority race/ethnic groups (Table 3).…”
Section: Discussionmentioning
confidence: 64%
“…For example, if estimated effects of NDI measured within the 8 km buffer size were particularly strong, our findings would provide evidence that NDI may operate on a large scale, and that the 8 km buffer was suitable for measuring neighborhood deprivation. Simulation (Spielman and Yoo, 2009) and an empirical study (Lovasi, et al, 2008) suggest that model fit has minimal utility as a criterion for the most appropriate neighborhood definition. We present overall model fit as corroboration of these prior findings, but focus discussion on the strength of the adjusted association.…”
Section: Methodsmentioning
confidence: 99%
“…The use of zip codes as an indicator for area-based socioeconomic context has received criticism in the scientific literature due to variations over time, size inconsistencies, and the neglect of other political, statistical or administrative boundaries 48. However, recent research has found that associations at the zip code level were similar to those found at smaller geographic definitions of neighborhood such as census tract and census block group levels 4950. Regardless of this support for the use of matching zip codes, we recognize that residual confounding could still occur and is a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…We use Wald tests to perform both sets of tests, and Appendix A.3 provides details on the test statistics. Smith et al (1995), Sobal et al (1996), Krieger et al (1999), Reijneveld et al (2000), Lorant et al (2001), Auchincloss and Hadden (2002), Flowerdew et al (2008), and Lovasi et al (2008) are all examples of work where using a Wald test statistic to test equality of estimates across different model specifications would have been useful; we found no examples in the literature where Wald tests were used.…”
Section: Popsizementioning
confidence: 79%